Implementasi Program Kartu Indonesia Sehat (Studi Kasus Pada Uptd Puskesmas Teluk Sasah Kecamatan Seri Kuala Lobam Kabupaten Bintan) (International Forum of Researchers and Lecturers, 2023)
The Healthy Indonesia Card (KIS) is one of the programs planned by Mr. President Joko Widodo and Vice President Mr. Jusuf Kalla on January 1 2014 ago, 14 days later, Mr. Joko Widodo and Jusuf Kalla were inaugurated as President and Vice President. The Healthy Indonesia Card (KIS) functions to provide health insurance for underprivileged/poor people to access health services free of charge. This study aims to find out how the Implementation of the Healthy Indonesia Card Program (Case Study at the UPTD Puskesmas Teluk Sasah, Seri Kuala Lobam District, Bintan Regency). This study uses a qualitative descriptive approach with primary and secondary data sources and data collection techniques using field observations, interviews, literature studies and documentation. This study uses Edwards III's theory with four indicators, namely communication, resources, disposition, and bureaucratic structure. The research results are based on the first indicator, namely the UPTD Teluk Sasah Health Center has provided information about Karu Indonesia Sehat to people seeking treatment in the area of Teluk Sasah Health Center by conducting outreach through the mass media. The second indicator is Resources, there are two resources in the implementation of the Healthy Indonesia Card program, namely human resources and financial resources. It is said that human resources are still lacking and financial resources such as facilities and infrastructure are sufficient. The third indicator is the disposition that the characteristics of the implementation of the Healthy Indonesia Card program are commitment, honesty, responsibility and fairness. The fourth indicator is the Bureaucratic Structure in which the implementation of the Indonesia Seat Card program has been carried out in accordance with the Standard Operating Procedures. The results of this study indicate that the Implementation of the Healthy Indonesia Card Program at the UPTD Puskesmas Teluk Sasah, Seri Kuala Lobam District, Bintan Regency has been implemented in a optimal.